Exhaust Valve Leakage Analysis on Main Engine at KM. Tonasa Lines XV - Driaskoro Budi Sidharta; Paulina M Latuheru (Politeknik Transportasi Sungai, Danau dan Penyeberangan Palembang, 2023)
The exhaust valve is one of the components on the main engine that functions to close and open the flow of exhaust gas from the combustion chamber or liner, both in four-stroke and two-stroke diesel engines. The research was carried out for Â±10 months on the Tonasa Line XV ship. The purpose of this study was to determine the cause of the exhaust valve leak. Primary data were obtained directly through interviews with related parties. Secondary data is obtained from data collection institutions and published to the data user community, in this study in the form of journals in e-journals. The results obtained from research identification show that first: the occurrence of spindle and seat valve wear due to a lack of maintenance systems, second: excess working hours of exhaust valves, third: clogged cooling water system. The identification of the research found that the cause of the exhaust valve leak was due to worn spindle and seat valves, excess working hours and blockage of the cooling water path. The ways that can be done to avoid damage are by grinding the spindle and seat valve, maintenance according to working hours, and cleaning the cooling water.